2004
DOI: 10.1534/genetics.166.3.1503
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Loci and Epistases Control Genetic Variation for Seed Dormancy in Weedy Rice (Oryza sativa)

Abstract: Weedy rice has much stronger seed dormancy than cultivated rice. A wild-like weedy strain SS18-2 was selected to investigate the genetic architecture underlying seed dormancy, a critical adaptive trait in plants. A framework genetic map covering the rice genome was constructed on the basis of 156 BC 1 [EM93-1 (nondormant breeding line)/ /EM93-1/SS18-2] individuals. The mapping population was replicated using a split-tiller technique to control and better estimate the environmental variation. Dormancy was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
204
4
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(220 citation statements)
references
References 48 publications
9
204
4
3
Order By: Relevance
“…Some dormancy QTLs in cultivated rice lost their effect upon drying (Lin et al, 1998). Dormancy QTLs identified from weedy rice could be grouped into relatively early, constant, and late expression categories during afterripening (Gu et al, 2004), which was similar to that from Arabidopsis (Alonso-Blanco et al, 2003). Thus, time of afterripening is an important environmental factor affecting expression of dormancy genes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some dormancy QTLs in cultivated rice lost their effect upon drying (Lin et al, 1998). Dormancy QTLs identified from weedy rice could be grouped into relatively early, constant, and late expression categories during afterripening (Gu et al, 2004), which was similar to that from Arabidopsis (Alonso-Blanco et al, 2003). Thus, time of afterripening is an important environmental factor affecting expression of dormancy genes.…”
Section: Introductionmentioning
confidence: 85%
“…Many dormancy QTLs have been identified from model plants and major cereal crops. For example, dormancy QTLs are distributed over all five chromosomes (chr) in Arabidopsis (Arabidopsis thaliana) ( Van der Schaar et al, 1997;Alonso-Blanco et al, 2003;Clerkx et al, 2004) and 11 of the 12 chr in cultivated (Oryza sativa) (Wan et al, 1997;Lin et al, 1998;Dong et al, 2002;Miura et al, 2002), wild (O. rufipogon) (Cai and Morishima, 2000;Thomson et al, 2003), and weedy (O. sativa) (Gu et al, 2004) rice. Dormancy QTLs in barley (Oberthur et al, 1995;Li et al, 2003;Prada et al, 2004), sorghum (Lijavetzky et al, 2000), and wheat (Anderson et al, 1993;Kato et al, 2001;Mares and Mrva, 2001;Groos et al, 2002;Osa et al, 2003;Kulwal et al, 2004) have been identified to seek gene resources to impart resistance to preharvest sprouting (PHS) and to manipulate germination programs in the malting process.…”
Section: Introductionmentioning
confidence: 99%
“…The same formula applied to all storage periods. Seed germination capability was transformed by sin -1 (x) -0.5 for statistical analysis (Gu et al, 2004).…”
Section: Seed Production and Field Experimentsmentioning
confidence: 99%
“…Weed control is a crucial part of an efficient crop production system, which can be facilitated by new methods to break seed dormancy (Gu et al, 2004). It is important to predict the weed seed dormancy in terms of timing and degree of weed emergence under field conditions to develop appropriate weed management approaches.…”
Section: Introductionmentioning
confidence: 99%